Pengaruh Pengetahuan dan Dampak Pernikahan Dini di Desa Kerta Dewa Kabupaten Musi Rawas Utara Tahun 2024 - Sirait, Betty; Triana, Neni (JURNAL KESEHATAN TERAPAN, 2024)
Marriage is an important thing in life. From marriage, a person will be able to achieve more balance in life, both biologically,psychologically and socially. The high number of cases of young marriage in Indonesia tends to occur in many villages due to the poor level of knowledge of the village population. This is because people who live in rural areas still have little knowledge about the dangers of underage marriage. Marriages at this age are mostly carried out by women with low educational status and who also come from families with low economic status. The aim of this research is to look at the influence of knowledge about early marriage and the impact of early marriage in Kerta Dewa Musi Rawas Village, North Lubuk Linggau in 2024. Research method This research method uses a qualitative-descriptive approach. Qualitative is an approach that underlies a socialphenomenon that exists in human life or patterns that are analyzed against ordinary social phenomena by using the culture of the society concerned or obtaining an overview of the rules that apply. The key informant, namely the Head Kerta Dewa Village and teenagers who carry out underage marriages in Kerta Dewa Village, North Musi Rawas Regency and several residents under 35 years of age.Research conducted on women under 35 years of age showed that the majority of respondents, namely 20 people (100%) 14 people (70%) had the wrong level of knowledge and only around 6 people (30%) had the correct level of knowledge so that the majority of respondents (70%) had knowledge that was not good or correct. Meanwhile, knowledge is one of the important factors that influences the incidence of child marriage. Previous studies concluded that one of the factors that causes child marriage is the lack of good background knowledge (Aychiluhm et al, 2021). Efforts to increase knowledge must continue to be made in the community